10. CLINICAL, LABORATORY CHARACTERISTICS OF WHITMORE CHILDREN PATIENTS TREATED AT THE NATIONAL CHILD’EN'S HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Whitmore is an infectious disease caused by the bacteria Burkholderia pseudomallei in humans and animals. It is not common in children but has diverse clinical features, difficult to diagnose, and a high mortality rate.Objective: To describe the clinical and subclinical characteristics of Whitmore in patients treated at the National Children’s Hospital.Research methods: Retrospective and prospective descriptive study on 45 children diagnosed with Whitmore and treated at the National Children’s Hospital from January 1, 2017 to December 31, 2023.Results: Of the total 45 pediatric patients diagnosed with Whitmore. The number of patients ≤ 5 years old is 26 (57.8%), the male/female ratio is 2/1; 91.1% of patients have no underlying diseases. The most common clinical manifestation was angle-of-jaw abscess in 26/45 cases, accounting for 57.8%, and bacteremia in 12/45 cases, accounting for 26.7%. Septic shock accounted for 22.2% of children infected with Whitmore. The sensitivity rate of B. pseudomallei to Meropenem and Imipenem antibiotics was 100%. The resistance rate to Ceftazidime antibiotics was 2.5%; Amoxicillin/Clavulanic Acid was 5% and Trimethoprim/Sulfamethoxazole was 23.5%.Conclusions: Whitmore is common disease in the age group ≤ 5, with the most common clinical presentation being parotid abscess accounting for 57.8%. The rate of bacteria sensitive to Carbapenem was 100% and the resistance rate to Ceftazidime was 2.4%.
Keywords: Whitmore disease; B. pseudomallei; children patient; parotid abscess